Controlled synthesis of three dimensional hierarchical graphene nanostructures from metal complexes as an anode material for lithium-ion batteries. Issue 21 (20th May 2020) - Li, Xiuli; Zhang, Feng; Fei, Ban; Song, Yu; Zhai, Bin; Wang, Xiuying
Abstract : Three dimensional hierarchical graphene nanostructures with refined secondary structures and primary nanobuilding units are realized here via a metal complex strategy. Abstract : The construction of hierarchical nanostructures plays an important role in performance improvement and application expansion of advanced nanomaterials. The fabrication of three dimensional hierarchical graphene nanostructures (TGNs) with controlled primary building units and secondary structures is still a challenge in synthetic methodology, since it is difficult to achieve the necessary delicate arrangement of graphene. TGNs with controlled primary building units and secondary structures are realized here via a metal complex strategy. Ni-Based metal complexes with organic polybasic acid ligands are used as the precursors of the TGNs. The results show that the amount of Ni(CH3 COO)2 ·4H2 O determines the different morphologies and compositions of the metal complex precursors, which further determine the primary building units and secondary structures of the TGNs. The obtained TGNs can serve as excellent candidates for anode materials for lithium ion batteries to achieve superior electrochemical behaviors.